Spectromectric Analysis of Lymphocyte Cell for the Premature Detection of Leukemia by Surface Plasmonic Technique in Nanoplatform - Srinivas Rao, K.; Preeta Sharan, Dr.; Tiwari, Anil (International Journal of Engineering and Technology, 2018)
Detection of cancer at early stages has become a top priority in the field of medical science. The existingÂ detection methods require lot of routine tests to confirm that the sample is positive with cancer as there are chances ofÂ test results being pseudo- positive. This early stage detection of cancer will proved to be a godsend for those who are the victims of monstrous disease cancer. In this paper, we put forward a new approach for the detection of cancer at early stages by designing a 2-dimensional SPR based sensor for detailed spectral analysis of â€œLeukaemiaâ€ without using any biomarkers. As dielectric properties for cancer cells deviate from the normal cell, they can be identified and detected by implementing photonic approach. In the present work, design & simulations are done using FDTD. The shifts in the output waveforms and wavelengths have been recorded for a normal blood cell and cancerous cell respectively. It is observed from simulation that even for minute change in the RI of the bio analyte of interest and from which it is observed that there is a remarkable shift in the resonant wavelengths thus witnessing the ultra sensitivity of the design. Simulations are done using R-Soft CAD tool. The peak values and wavelength shift differences for normal cells andÂ forleukaemia, the different cell components lymphocyte , nucleus, cytoplasm and theÂ intensity shifts are recorded in order to find the relative sensitivity of the device. The design variation were madeÂ by varying sensing layer thickness and extinction coefficient Finally comparison was made between that of normal and abnormal cells to show the wavelength shift differences so that the signature graphs for each cell were obtained in order to determine the intensity of the disease and it depends on the shift in the wavelength.Â The wavelength shift of early stage leukaemia for cytoplasm, nucleus and lymphocyte are ranging from 2000-250nm. Sensitivity and the quality factor of the sensor have been calculated for the proposed design, the sensitivity achieved is 343nm/RIU and the quality factor is 1800.Â Â